Clinical strategies for addressing obesity in infants and toddlers. Issue 2 (February 2021) - Graf, Michelle D.; Karp, Sharon M.; Lutenbacher, Melanie; Wasser, Heather; Bushaw, Andrea; Dietrich, Mary S.
Abstract : Abstract: Babies' earliest food experiences have a lifelong impact on eating preferences and dietary habits, laying the foundation for obesity risk. NPs have the opportunity to provide education about healthy infant feeding practices before the growth trajectory becomes abnormal and focus intensive education on at-risk families. Abstract : Babies' earliest food experiences have a lifelong impact on eating preferences and dietary habits, laying the foundation for obesity risk. NPs have the opportunity to provide education about healthy infant feeding practices before the growth trajectory becomes abnormal and focus intensive education on at-risk families.